Exploring the implications of the first COVID‐19 lockdown on patients with melanoma: a national survey. (1st January 2022) - Raza, S. A.; Cannon, D.; Nuttall, G.; Ali, F. R.
Summary: The impact of the COVID‐19 pandemic upon care of malignant melanoma (MM) remains as yet poorly understood. We undertook a UK‐wide national survey, in conjunction with a patient support group (Melanoma UK), to explore patient perceptions of the impact of the pandemic upon treatment and outpatient care of their MM. Our findings suggest that following the onset of COVID‐19, a significant minority of treatments and appointments have been delayed, there has been a shift from face‐to‐face to virtual outpatient consultations and there may be a rise in psychological comorbidities in patients with MM. We would urge clinicians to consider mental health interventions as part of a holistic care package.